Fiscal policy in the Bundestag: Textual analysis and macroeconomic effects - Albina Latifi; Viktoriia Naboka-Krell; Peter Tillmann; Peter Winker (Philipps-University Marburg, School of Business and Economics, 2023)
Fiscal policy is made in parliament. We go to the roots of changes of fiscal policy in Germany and use a novel data set on all parliamentary speeches in the Bundestag from 1960 to 2021. We propose an embedding-based approach, which allows the representation of words and documents in a shared vector space, in order to measure fiscal policy-related sentiment in parliamentary debates at a scale from contractionary to expansionary. For this purpose, a dictionary containing terms related to expansionary and contractionary policy measures is created. We put fiscal sentiment into a series of recursively-identified vector autoregressive (VAR) models to show that a change in fiscal sentiment causes a change in government spending and has strong effects on the macroeconomy. The results support the notion that the debate in parliament contains information for the identification of government spending shocks.
Keywords: C89; E60; E62; 330; text mining; word embeddings; VAR models; identification; government spending